A Comparative Study on the Effectiveness of Unified Protocols for Transdiagnostic Treatment of Emotional Disorders and Modular Cognitive-Behavioral Therapy on Positive and Negative Affect, and Emotional Awareness in Children with Type 1 Diabetes Mellitus - Maryam Hashemipoor Zavareh; Mansoureh Bahramipour Isfahani; Ilnaz Sajjadian (Advanced Biomedical Research)
Background: This study aims to compare the effectiveness of unified protocols for transdiagnostic treatment of emotional disorders and modular cognitive-behavioral therapy on positive and negative affect and emotional awareness in children with Type 1 Diabetes (T1D). Materials and Methods: In this semi-experimental pretest-posttest study, T1D patients enrolled in two experimental groups: unified protocols for transdiagnostic treatment of emotional disorders and modular cognitive-behavioral therapy interventions in a unified process and one control group. After the completion of the therapeutic sessions, all three groups responded to the research questionnaires in the post-test phase and after a two-month follow-up and were compared. Results: The results of the repeated measures analysis of variance showed that the unified protocols for transdiagnostic treatment of emotional disorders and modular cognitive-behavioral therapy interventions had a significant effect on increasing positive affect and emotional awareness, as well as reducing negative affect in children with T1D, and the effects of the treatment remained during the follow-up stage (P < 0.001). A comparison between the two treatments also indicated that the modular cognitive-behavioral therapy intervention had a greater effectiveness in reducing the negative affect variable in the post-test phase compared to the unified protocols for transdiagnostic treatment (P < 0.01). There were no significant differences between the two therapeutic methods in other variables (P > 0.05). Conclusions: Based on these findings, both interventions can be used as useful treatments to improve psychological variables in children with T1D. These results underscore its potential as a potent tool for enhancing the emotional well-being of individuals with this condition, thereby contributing to an improved quality of life.